Negotiating queer and religious identities in higher education: queering 'progression' in the 'university experience'. Issue 6 (18th August 2017) - Falconer, Emily; Taylor, Yvette
Abstract: This article addresses the negotiation of 'queer religious' student identities in UK higher education. The 'university experience' has generally been characterised as a period of intense transformation and self-exploration, with complex and overlapping personal and social influences significantly shaping educational spaces, subjects and subjectivities. Engaging with ideas about progressive tolerance and becoming, often contrasted against 'backwards' religious homophobia as a sentiment/space/subject 'outside' education, this article follows the experiences and expectations of queer Christian students. In asking whether notions of 'queering higher education' (Rumens 2014 ) 'fit' with queer-identifying religious youth, the article explores how educational experiences are narrated and made sense of as 'progressive'. Educational transitions allow (some) sexual-religious subjects to negotiate identities more freely, albeit with ongoing constraints. Yet perceptions of what, where and who is deemed 'progressive' and 'backwards' with regard to sexuality and religion need to be met with caution, where the 'university experience' can shape and shake sexual-religious identity.